Evaluation of the adverse effects of Dracaena steudneri Engl. stem bark aqueous extract in Wistar rats - Tenywa, Mercy Gladys; Katuura, Esther; Tolo, Casim Umba; Ajayi, Clement Olusoji; Agaba, Amon Ganafa (African Journal of Pharmacy and Pharmacology, 2021)
Safety of medicinal plants/products is one of the major areas that require more attention because of the high rate at which consumers use medicinal plants/products due to their availability and accessibility. Dracaena steudneri Engl. is among the plants being used and recommended for the treatment of several diseases for decades among the traditional health practitioners. Despite its frequent use, there is little literature on its safety. This study investigated the acute and sub-acute effects of D. steudneri Engl. stem bark with a view to establishing its safe dose for drug development. The stem bark of D. steudneri Engl (Dracaenaceae) was collected, authenticated, dried, pulverized mechanically and extracted using decoction method. The extract was thereafter concentrated in vacuo at 50°C using rotary evaporator and lyophilised. The acute test was studied in Wistar rats using Lorke’s method at 10 to 5000 mg/kg to determine the lethal dose (LD50) and other adverse effects including weight loss, body scratching etc. In sub-acute test, 24 Wistar rats of both sexes were separately caged and orally administered with extract at 25 to 100 mg/kg. The administration was repeated for 28 days before the animals were humanely sacrificed. Blood of each animal was collected for hematological and biochemical examination, while the essential organs were harvested for histopathologic. The results showed that LD50 was greater than 5000 mg/kg. The extract did not exhibit any significant difference (p>0.05) on hematological parameters when compared with the negative control. There was no degenerative effect in the histology and pathology of all the organs examined but elevation in serum ALT and creatinine levels was observed. Although the aqueous extract of D. stuedneri stem bark did not show any significant hematological and histopathological effect on the organs tested, there was potential for renal and hepatic toxicity after repeated administration. Therefore caution must be taken with close monitoring during prolonged administration..
Keywords: Acute; Safety; Dracaena steudneri; Sub-acute; Toxicity